Theoretical and methodological foundations for studying the problems of developing social resources of territorial communities - N. O. Sokolova (Вестник Майкопского государственного технологического университета)
The article is devoted to the development of theoretical and methodological foundations for studying the problems of developing social resources of territorial communities. The relevance of the research is due to the social order formed in modern society for the effective and optimal use of the social resources available in the territory as the basis for development. The purpose of the research is to determine theoretical and methodological foundations for studying the problems of developing social resources of territorial communities. Theoretical substantiation and research methods were laid by the works of domestic and foreign sociologists who substantiated the importance of the resource approach for the development of socio-economic systems. The application of system analysis made it possible to reveal the interdependence of the development of social resources and the territory. The totality of the components of the social resources of an individual, proposed by V.A. Yadov, most meaningfully reflects the targets of this research. In this regard, it has been proposed to use this material for the formation of sociological tools for obtaining primary information (questionnaires). The use of statistical data makes it possible to obtain an objective idea of the state of the environment and the main trends in territorial development. The systematization of factual and evaluative data has significant potential, which will be realized as part of the construction of a research construct. Summarizing, it can be said that the complexity and diversity of the concept of «social resources» is projected onto the process of forming the methodological foundations of the research. A systematic approach allows us to turn to the analysis of subjective and objective data and compare the received materials. Relying on the resource approach, it is possible to formulate measures to improve the development efficiency of both the territorial community as a whole and individual component of social resources.